Extraction and Characterization of Corn Leaf Fiber. Issue 5 (4th May 2022) - Singh, Garima; Jose, Seiko; Kaur, Devinder; Soun, Bhawna
ABSTRACT: Corn leaves were collected after harvesting corn and the fibers were extracted by water retting. The fibers were subjected to alkali treatment in order to enhance the mechanical as well as handle properties. The physico-mechanical properties of the retted and alkali-treated corn leaf fibers were analyzed using various analytical and statistical methods. The change in chemical composition due to alkali treatment was determined using Fourier transmission infrared spectroscopy and chemical composition analysis. Results inferred that 15 days retting gives better quality of fibers. The alkali treatment resulted in the removal of lignin, fats, and waxes as well as the disintegration of individual fibers from the retted fiber bunch. Bundle strength, elongation, and moisture properties were found to improve after chemical treatment. The study shows that corn leaf fiber has good potential in technical textile applications.